HOW THE ECONOMIC CRISIS AFFECTS THE ENVIRONMENT? - BARBU, Cristina (Journal of Environmental Management and Tourism, 2016)
Over the last twenty years Romania’s economy has grown. Many zones have reduced poverty and improved education. During the last two years, industrial production has been affected by the crisis. There are both immediate and long-term positive and negative environmental implications of the crisis. Some of researchers think that the decline in production will automatically lead to a lower level of pollution. On the contrary, other researchers think that the problem of pollution may become worse during the crisis period. In our country, environmental protection seems to have a lower priority but the sustainable development is no longer a “choice”.